2015
DOI: 10.1007/s00586-015-3872-7
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of lordosis restoration with anterior longitudinal ligament release and lateral hyperlordotic cage placement

Abstract: Increased segmental lumbar lordosis is achievable with hyperlordotic cages after ALL resection. Increased cage height tended to increase the amount of lordosis achieved, although in some cases additional posterior bone resection was required to maximize lordosis. Further studies are needed to evaluate the impact on regional lumbar lordosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…With the advent of lateral grafts with 20°-30° of angulation and sectioning of the ALL, 29 however, much more profound focal and regional curvature can be obtained, typically averaging about 50% of the inserted graft angle (10°-17°). 11,14,41,71,73,75 Case series have demonstrated that the procedure can be performed safely, with blood loss ranging from 40 to 150 ml and with a complication rate similar to that observed with standard lateral transpsoas approaches. 11,29,58 This technique does have some limitations, however, as it generally cannot be used in cases of previous posterior fusion without some form of release, and almost never in cases of a previous interbody fusion unless a pseudarthrosis is present.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of lateral grafts with 20°-30° of angulation and sectioning of the ALL, 29 however, much more profound focal and regional curvature can be obtained, typically averaging about 50% of the inserted graft angle (10°-17°). 11,14,41,71,73,75 Case series have demonstrated that the procedure can be performed safely, with blood loss ranging from 40 to 150 ml and with a complication rate similar to that observed with standard lateral transpsoas approaches. 11,29,58 This technique does have some limitations, however, as it generally cannot be used in cases of previous posterior fusion without some form of release, and almost never in cases of a previous interbody fusion unless a pseudarthrosis is present.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Mechanistically, excessive stress secondary to imbalance in the sagittal plane exhausts the posterior spinal muscles, translating to lower back pain. 34,53,54 We propose 3 augmenting strategies for CMIS correction of sagittal balance using hyperlordotic cages: (1) utilizing appropriately angled cages, (2) anterior positioning of the implant in the disc space, and (3) concentrating Table 4. Mean segmental lordosis grouped by lordotic angle of cage.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Novel innovations have been introduced to tackle the problem of sagittal alignment. These include anterior column realignment (ACR), [34][35][36][37][38][39][40][41] rod contouring, 42,43 and the utilization of hyperlordotic cages. 34,38 These are designed to maximize the sagittal correction achievable with CMIS techniques while maintaining the many benefits that MIS operations offer.…”
Section: -17mentioning
confidence: 99%
See 1 more Smart Citation
“…Uribe et al (30), in their 3D model of the spine, resected ALL via a lateral approach and using hyperlordosis cages of 20 and 30 degrees, demonstrated improvement of lordosis of almost 7 and 11 degrees respectively. Deukmedjian et al (31) in their series of 7 patients showed an increase in segmental lordosis of 17 degrees with ALL released and the use of hyperlordosis cages via XLIF approach.…”
Section: Segmental Lordosismentioning
confidence: 99%